Energy, Resolution and Efficiency Calibration of a LaBr3(Ce) Scintillator - Ntalla, Eleni; Clouvas, Alexandros; Savvidou, Anastasia (HNPS Advances in Nuclear Physics, 2019)
The last decade LaBr3(Ce) scintillation detectors have become commercially available and have better scintillation properties (energy resolution, temperature performance, decay time, light yield and material density) when compared with NaI(Tl) scintillators. The aim of this work is the full calibration (energy, resolution and efficiency) of a 1.5x1.5 in LaBr3(Ce) Canberra scintillator. Energy and resolution calibration were performed experimentally with the use of point sources with a source-detector distance at 22 cm. MCNPX simulations were performed in order to evaluate the efficiency calibration for three different source-detector geometries and then they were validated by the experimental efficiencies estimation.